2015
DOI: 10.1037/hea0000140
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI risk-reduction intervention efficacy with South African adolescents over 54 months.

Abstract: Objective Little research has tested HIV/STI risk-reduction-interventions’ effects on early adolescents as they age into middle and late adolescence. This study tested whether intervention-induced reductions in unprotected intercourse during a 12-month period endured over a 54-month period and whether the intervention reduced sexually transmitted infections (STIs), which increase risk for HIV. Method Grade-6 learners (mean age = 12.4 years), participants in a 12-month trial in Eastern Cape Province, South Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…The cluster size ranged from 18 to 461 participants. One trial was conducted in Latin America (Chile, Cabezón 2005 CHL), two trials in Europe (England (Stephenson 2008 GBR), and Scotland (Henderson 2007 GBR)), and five in sub-Saharan Africa (Malawi (Baird 2012 MWI), Zimbabwe (Cowan 2010 ZWE), Kenya (Duflo 2015 KEN), South Africa (Jemmott 2015 ZAF), and Tanzania (Ross 2007 TZA). Of those conducted in Africa, two were in rural areas (Cowan 2010 ZWE; Ross 2007 TZA), and three were in both rural and urban areas (Baird 2012 MWI; Duflo 2015 KEN; Jemmott 2015 ZAF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cluster size ranged from 18 to 461 participants. One trial was conducted in Latin America (Chile, Cabezón 2005 CHL), two trials in Europe (England (Stephenson 2008 GBR), and Scotland (Henderson 2007 GBR)), and five in sub-Saharan Africa (Malawi (Baird 2012 MWI), Zimbabwe (Cowan 2010 ZWE), Kenya (Duflo 2015 KEN), South Africa (Jemmott 2015 ZAF), and Tanzania (Ross 2007 TZA). Of those conducted in Africa, two were in rural areas (Cowan 2010 ZWE; Ross 2007 TZA), and three were in both rural and urban areas (Baird 2012 MWI; Duflo 2015 KEN; Jemmott 2015 ZAF).…”
Section: Resultsmentioning
confidence: 99%
“…All included trials reported at least one of the main outcome measures. However, one trial did not include the data in the final published paper and we were unable to get this data for inclusion in the review despite contacting the trial authors (Jemmott 2015 ZAF). …”
Section: Methodsmentioning
confidence: 99%
“…Information about the procedures, recruitment, consent, interventions, and findings of the trial has been previously reported (J. B. Jemmott, 3rd, et al, 2010; J. B. Jemmott, 3rd, & Jemmott, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, this study uses 54-month follow-up data from a sexual risk-reduction intervention trial conducted in Eastern Cape Province, South Africa with sixth-grade adolescents (J. B. Jemmott, 3rd et al, 2010; J. B. Jemmott, 3rd, & Jemmott, 2015).…”
mentioning
confidence: 99%
“…Randomly selected neighborhoods were randomized to the Men Together Making a Difference health-promotion intervention or a HIV/STI risk-reduction intervention, which in this article serves as an attention-matched control group. The health-promotion intervention was developed based on the theory of planned behavior (Ajzen, 1991; Armitage and Conner, 2001; Hagger et al, 2002; McEachan et al, 2011), a theory selected for its ease of adaptation to different cultures and behaviors (Jemmott, 2012) and its utility in efficacious interventions (Darker et al, 2010; Montanaro and Bryan, 2014; Plotnikoff et al, 2014; Zhang et al, 2009), including interventions in South Africa (Heeren et al, 2013; Jemmott et al, 2011; Jemmott et al, 2014c). The health-promotion intervention significantly increased self-reported adherence to physical-activity guidelines averaged over the 6- and 12-month post-intervention assessments, which was the primary outcome, compared with the attention-control group (Jemmott et al, 2014a).…”
mentioning
confidence: 99%